2014
DOI: 10.1080/08964289.2014.947234
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Risk Awareness and Concern among Women with a Family History of Breast or Ovarian Cancer

Abstract: Women with a documented deleterious mutation in BRCA1 or BRCA2 are at substantially elevated risk for ovarian cancer. To understand what percentage of women with high risk family histories know their risk is elevated we surveyed 1,885 women with a high or moderate risk family history and no personal history of breast or ovarian cancer, and asked about their perceived risk of breast and ovarian cancer. Among high-risk women, fewer than 20% reported use of genetic counseling, and knowledge of elevated risk of ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…[ 26 ] Hence, it is the individuals with high awareness who try to gain healthy lifestyle behaviors and seek medical attention timely when they get sick. [ 27 ] People with a family history of cancer experience a fear of getting cancer, and they try to reform their lives to avoid risk factors that can cause cancer and maintain their lives as such in order not to get cancer. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Hence, it is the individuals with high awareness who try to gain healthy lifestyle behaviors and seek medical attention timely when they get sick. [ 27 ] People with a family history of cancer experience a fear of getting cancer, and they try to reform their lives to avoid risk factors that can cause cancer and maintain their lives as such in order not to get cancer. [ 22 ]…”
Section: Discussionmentioning
confidence: 99%
“…The background genetic testing rate in control group of 9% over 2 years women confirms prior reports that many high-risk women do not receive guideline recommended care 20 . Fewer than 20% of eligible women reported having had genetic counseling, and most women (> 75%) were unaware of their elevated risk for ovarian cancer 8 . Among those that enrolled in the study, roughly 20% reported having a first or second-degree relative with ovarian cancer and therefore meet current guidelines for genetic testing 4 .…”
Section: Discussionmentioning
confidence: 99%
“…20 Fewer than 20% of eligible women reported having had genetic counseling, and most women (>75%) were unaware of their elevated risk for ovarian cancer. 8 Among those who enrolled in the study, roughly 20% reported having a first-degree or second-degree relative with ovarian cancer and thus meet current guidelines for genetic testing. 4 Compliance with the genetic counseling referral was good at 85%, possibly in part because it was offered at no cost during the trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, breast cancer is more common and mainly happened among women. Yearly the total number of new cases of breast cancer diagnosed around the world exceeds one million [1]. In Malaysia, breast cancer is considered the most common cancer diagnosed among women, it represents 31% of the total number of newly diagnosed cancer cases [2].…”
Section: Introductionmentioning
confidence: 99%